Effect of temperature on the reproduction of Bracon vulgaris Ashmead (Hymenoptera: Braconidae), a parasitoid of the cotton boll weevil - Francisco S. Ramalho; Paulo A. Wanderley; José B. Malaquias; Francisco S. Fernandes; Antônio R.B. Nascimento; José C. Zanuncio (Anais da Academia Brasileira de Ciências, 2011)
This research studied the effect of temperature on the reproduction of Bracon vulgaris Ashmead, an ectoparasitoid of cotton boll weevil ( Anthonomus grandis Boheman) at constant temperatures of 20, 25 and 30ºC, 70 ± 10% RH and a photophase of 14 h. Females of the parasitoid produced a greater number of eggs when exposed to 25ºC (124.65 eggs) in relation to those exposed to 20 (43.40 eggs) and 30ºC (49.60 eggs). The number of parasitized larvae per female of B. vulgaris at 25ºC (71.75) was greater than at 20ºC (31.40) and 30ºC (25.15). The daily intrinsic rates of increase (r m) were - 0.007 at 20ºC, 0.07 at 25ºC and 0.03 at 30ºC, revealing that the temperature of 25ºC produced increases of 1,100 and 133% in the value r m in relation to temperatures of 20 and 30ºC, respectively. In programs of biological control of the boll weevil using innoculative releases, adult females of B. vulgaris with approximately five (at 25 or 30ºC) or 20 day old (at 20ºC) should be used; when using innundative releases, adult females of B. vulgaris , with ages between 11 and 31; 9 and 29 or 3 and 14 days, respectively, at 20, 25 or 30ºC should be used. Estudamos os efeitos da temperatura na reprodução de Bracon vulgaris Ashmead, ectoparasitóide do bicudo-do-algodoeiro, Anthonomus grandis Boheman, em câmaras climatizadas, em temperaturas constantes de 20, 25 and 30ºC, umidade relativa do ar de 70 ± 10% e fotofase de 14 h. As fêmeas do parasitóide produziram mais ovos a 25ºC (124,65 ovos) do que aquelas expostas a 20 (43,40 ovos) e a 30ºC (49,60 ovos). O número médio de larvas parasitadas por fêmea de B. vulgaris a 25ºC(71,75 larvas) foi maior do que a 20ºC (31,40 larvas) e 30ºC (25,15 larvas). As taxas diárias de aumento (r m) foram -0,007 a 20ºC, 0,07 a 25ºC e 0,03 a 30ºC, indicando que a temperatura de 25ºC produziu aumento de 1100 e 133% no valor de r m em relação às temperaturas de 20 e 30ºC, respectivamente. Nos programas de controle biológico do bicudo-do-algodoeiro, usando liberações inoculativas deve-se utilizar fêmeas adultasde B. vulgaris com aproximadamente 5 dias (a 25 ou 30ºC) ou 20 dias de idade (a 20ºC); quando usando liberações inundativas, utilizar fêmeas adultas de B. vulgaris , com idade entre 11 e 31 dias (a 20ºC); 9 e 29 dias (a 25ºC) ou 3 e 14 dias (a 30ºC).